Dialogicidade entre os mundos da educação e do trabalho no processo de Formação em fisioterapia - Silva, Eveline de Almeida (2015)
The changes imposed on society and to work itself in consequence of globalization exposed health professionals to an environment full of demands and expectations due to the spread of new technologies and continuous requirements for adaptations to the new work processes. Currently, there are still important gaps to be clarified about the interaction between the worlds of work and education. In face of this reality, this scientific research had as object of study the skills and abilities that guide the formative process of the physiotherapist as director of professional practice, justified by the need to form a qualified and skilled professional in terms of technical activities, but also capable to evaluate the situation since its political origins to the immediate and mediate results in primary, secondary and tertiary health care. Thus, it became an objective to evaluate the connection between the worlds of education and work based on the skills and abilities proposed in the National Curriculum Guidelines for the development process of physiotherapists. The study was exploratory, observational, descriptive and inferential with quantitative and qualitative approaches, performed in higher education institutions that offer undergraduate courses in Physiotherapy, located in the city of João Pessoa and Campina Grande, in which the target population brought together 463 participants, being 370 of them students and 93 professors. The qualitative analysis was subsidized by the speech analysis technique which made it possible to identify the gaps analyzed in the context of the labor activities, through the positioning of seven representatives of the working world. In quantitative analysis, methods of factor analysis were used and cluster analysis that demonstrated the gaps particularly in the following expertise and general skills, Administration and Management, Communication, Permanent Education and Leadership, and within the scope of expertise and general skills, gaps on items VI and XII. Therefore, it was confirmed the assumption that physiotherapists don’t use the expertise and skills proposed by the world of education or do it in some extent, proving the need for constant revisions of the National Curriculum Guidelines regarding the lack of dialogicity between the worlds of work and education.